Dynamic numerical simulation for ship-OWT collision - Nianxin Ren; Jinping Ou (2009 8th International Conference on Reliability, Maintainability and Safety, 2009)
At present, more and more offshore wind farms have been built and numerous projects are on the drawing tables. Therefore, the study on the safety of collision between ships and offshore wind turbines (OWT) has great practical significance. The present study takes the advantage of the famous LS-DYNA explicit code to simulate the dynamic process of the collision between a typical 3MW offshore wind turbine model with monopile foundation and a simplified 2000t-class ship model. In the simulation, the added mass effect of the ship, contact nonlinearity of collision, material nonlinearity of steel and adaptive mesh for large structure deformation have been taken into consideration. A new conceptual sphere-shell crashworthy device for OWT is proposed, and the good performance of the new device under ship-OWT front impact and side impact has been verified from both views of theoretical analysis and numerical results. The sphere-shell crashworthy device can use its own structure deformation to absorb the collision energy from the ship. As a result, the key structure of the OWT and the electric control equipments contained in it can be saved by scarifying the structural plastic deformation of new sphere crashworthy device. Moreover, in the collision, the damage of the ship could also be reduced to a great degree due to the sphere configuration design of the crashworthy device.